CRE 3 - Periodic Functions | Algebra - Functions & Graphs
Answer the next 3 questions based on the information given below:
Is the given function periodic?
Type 1 for yes,
Type 2 for no.
Answer: 1
Explanation :
For a function to be periodic these should exist a real number p such that
f(p + x) = f(x).
Here, p = 12.5
Hence, 1.
Workspace:
Answer: 1
Explanation :
For a function to be periodic these should exist a real number p such that
f(p + x) = f(x).
Here, p ≈ 12.5
Hence, 1.
Workspace:
Answer: 2
Explanation :
For a function to be periodic these should exist a real number p such that
f(p + x) = f(x).
Here, the function keeps increasing on either side of y axis.
∴ This is not a periodic function.
Hence, 2.
Workspace:
Find the periodicity of the function f(x) = Sinθ.
- (a)
180°
- (b)
360°
- (c)
90°
- (d)
None of these
Answer: Option B
Explanation :
We know, Sin(360° + θ) = Sinθ.
∴ The value of f(x) repeats after every 360°.
⇒ Period of f(x) = 360°.
Hence, option (b).
Workspace:
Find the periodicity of the function f(x) = (Sinθ)2.
- (a)
180°
- (b)
360°
- (c)
90°
- (d)
None of these
Answer: Option A
Explanation :
Let us draw the graph of (Sinθ)2.
∴ From the graph we can see that the value of f(x) repeats after every πc i.e., 180°.
⇒ Period of f(x) = 180°.
Hence, option (a).
Workspace:
Let g(x) be a function such that g(x + 1) + g(x - 1) = g(x) for all x. For which value of p is the relation g(x + p) = g(x) necessarily true for all x?
- (a)
5
- (b)
3
- (c)
2
- (d)
6
Answer: Option D
Explanation :
Suppose g(1) = a and g(2) = b
Given, g(x + 1) + g(x - 1) = g(x)
⇒ g(x + 1) = g(x) – g(x – 1)
Put x = 2, g(3) = b - a
Put x = 3, g(4) = (b - a) – b = -a
Put x = 4, g(5) = -a – (b - a) = -b
Put x = 5, g(6) = -b – (-a) = a - b
Put x = 6, g(7) = (a – b) – (-b) = a
Put x = 7, g(8) = a – (a - b) = b
… and so on.
Based on this patter we can notice that the value of f(x) repeats after every 6 terms.
∴ f(6 + x) = f(x).
⇒ p = 6
Hence, option (d).
Workspace:
If g(x) = g(x - 1) × g(x + 1) and g(0) = 1/3 and g(5)= 1/6, then g(1 + 2 + 3 + … + 100) =
- (a)
1/3
- (b)
1/2
- (c)
(1/3) × (1/6) × (1/9) ×…× (1/300)
- (d)
None of these
Answer: Option B
Explanation :
Given, g(x) = g(x - 1) × g(x + 1) and g(0) = 1/3.
⇒ g(x + 1) = g(x)/g(x - 1)
Suppose g(1) = a
Put x = 1, we get g(2) = a/(1/3) = 3a.
Put x = 2, we get g(3) = 3a/a = 3.
Put x = 3, we get g(4) = 3/3a = 1/a
Put x = 4, we get g(5) = (1/a)/3 = 1/3a
Also it is given, g(5) = 1/6
∴ 1/3a = 1/6
⇒ a = 2.
∴ g(4) = 1/2 and g(5) = 1/6
Put x = 5, we get g(6) = (1/6)/(1/2) = 1/3 = g(0)
Put x = 6, we get g(7) = (1/3)/(1/6) = 2 = g(1)
Hence, we can see that g(6 + x) = g(x).
∴ g(1 + 2 + 3 + … + 100) = g(5050) = g(6 × 841 + 4) = g(4) = ½
Hence, option (b).
Workspace:
Feedback
Help us build a Free and Comprehensive Preparation portal for various competitive exams by providing us your valuable feedback about Apti4All and how it can be improved.